Herbicides Physiology of Action and Safety - Price, Andrew; Kelton, Jessica; Sarunaite, Lina (IntechOpen, 2015)
Herbicides are one of the most widely used groups of pesticides worldwide for controlling weedy species in agricultural and non-crop settings. Due to the extensive use of herbicides and their value in weed management, herbicide research remains crucial for ensuring continued effective use of herbicides while minimizing detrimental effects to ecosystems. Presently, a wide range of research continues to focus on the physiology of herbicide action, the environmental impact of herbicides, and safety. The authors of Herbicides, Physiology of Action, and Safety cover multiple topics concerning current valuable herbicide research.